Role of the sources of Islamic Law in codification and formation of the Mecelle (Majallah) - Kayadibi, Saim (2017)
The greatest contribution of the Ottomans to codification and formation of Islamic law which has brought to the legal literature is of course the Mecelle (Majallah). It is still the most serious work of its kind in the circumstances of the time when the Western world's political and legal effects on the Islamic world are taken into consideration. It is obvious that a lots of serious works and self-sacrifice have been made for the achievement of the formation of Islamic law. The formation of Islamic law, which encompasses a few centuries, has undertaken serious task of formulating the unique methods of different law schools which indirectly laid the groundwork for the codification and formulation of the rules of Islamic law. Likewise, the fact that the sources of Islamic Law which have been formulated in a concrete manner has created logic of law, and it persuaded the jurists to make the laws easily be understandable following the formulation of the principles of Islamic Jurisprudence (uṣūl al-fıqh). The role that Islamic law has played with serious works towards responding the legal needs of the Muslim society for centuries cannot be denied. In this context, it is known that Islamic law has been playing a significant role in shaping the Muslim society since the beginning of the revelation. This paper, therefore, focuses on the role that the sources of Islamic law played in the codification and formulation of the Mecelle.